Pengembangan Pendekatan Kolaboratif dengan Model Pembelajaran Berbasis Digital untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Puspa Nurhaliza, Adinda; Damayanti, Lidya; Hartanti, Rani; Iskandar, Sofyan (CV. Pusdikra Mitra Jaya, 2025)
This study aims to determine the increase in student learning interest using the development of a collaborative approach with a digital-based learning model. The collaborative approach is a procedure in which students learn together in groups directed towards achieving collective goals so that they are accustomed to thinking critically and analytically in order to avoid conceptual errors and confusion of understanding. Then in addition to the collaborative approach, the digital learning model also plays a role to deliver learning materials, provide learning media, and also facilitate two-way interaction between teachers and students by utilizing e-learning (digital technology) such as computers, the internet, software, and applications to support and modify learning to make it look more innovative. Therefore, e-learning can be an effective tool in digital learning especially in increasing students' interest in learning. Collaborative approach with digital-based learning model has an important role as an important and effective method for learning because it allows exploration of the subject through social interaction among peers as well as between students and teachers. In her research, the researcher used a qualitative method with a literature study approach in the form of data collection from various research sources of experts. The results showed that a collaborative approach with a digital-based learning model was able to increase elementary school students' interest in learning.